Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve for the variables \( m \) and \( n \) given the two equations:
[tex]\[ 2^m \times \left(\frac{1}{8}\right)^n = 128 \][/tex]
[tex]\[ 4m \div 2 - 4m = \frac{1}{16} \][/tex]
We'll approach this step by step.
### Step 1: Simplify the Second Equation
Starting with the second equation:
[tex]\[ 4m \div 2 - 4m = \frac{1}{16} \][/tex]
Dividing \( 4m \) by 2 simplifies to \( 2m \):
[tex]\[ 2m - 4m = \frac{1}{16} \][/tex]
Combine like terms:
[tex]\[ -2m = \frac{1}{16} \][/tex]
Solving for \( m \):
[tex]\[ m = -\frac{1}{32} \][/tex]
### Step 2: Substitute \( m \) into the First Equation
Now, we substitute \( m = -\frac{1}{32} \) into the first equation:
[tex]\[ 2^m \times \left(\frac{1}{8}\right)^n = 128 \][/tex]
First, express \( \frac{1}{8} \) as a power of 2:
[tex]\[ \frac{1}{8} = 2^{-3} \][/tex]
The first equation now becomes:
[tex]\[ 2^m \times (2^{-3})^n = 128 \][/tex]
Simplify the exponent on the left side:
[tex]\[ 2^m \times 2^{-3n} = 128 \][/tex]
Combine the exponents:
[tex]\[ 2^{m-3n} = 128 \][/tex]
Now, express 128 as a power of 2:
[tex]\[ 128 = 2^7 \][/tex]
So the equation simplifies to:
[tex]\[ 2^{m - 3n} = 2^7 \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ m - 3n = 7 \][/tex]
### Step 3: Solve for \( n \) using \( m = -\frac{1}{32} \)
Substitute \( m = -\frac{1}{32} \) into the exponent equation:
[tex]\[ -\frac{1}{32} - 3n = 7 \][/tex]
Add \(\frac{1}{32}\) to both sides:
[tex]\[ -3n = 7 + \frac{1}{32} \][/tex]
To add the fractions, convert 7 to a fraction with the same denominator:
[tex]\[ 7 = \frac{224}{32} \][/tex]
So:
[tex]\[ -3n = \frac{224}{32} + \frac{1}{32} \][/tex]
[tex]\[ -3n = \frac{225}{32} \][/tex]
Divide both sides by -3:
[tex]\[ n = -\frac{225}{32 \times 3} \][/tex]
[tex]\[ n = -\frac{225}{96} \][/tex]
Simplify \(-\frac{225}{96}\):
[tex]\[ n = -\frac{225}{96} = -\frac{75}{32} \][/tex]
### Step 4: Box the Solutions
We have found that:
[tex]\[ m = -\frac{1}{32} \][/tex]
[tex]\[ n = -\frac{75}{32} \][/tex]
So, the solutions are:
[tex]\[ m = -0.03125 \][/tex]
[tex]\[ n = -2.34375 \][/tex]
Comparing this with the given results, we have the following possible solutions:
1. \( m = -0.03125 \), \( n = -2.34375 \)
2. \( m = -0.03125 \), \( n = -2.34375 - 3.0215734278848i \)
3. \( m = -0.03125 \), \( n = -2.34375 + 3.0215734278848i \)
Thus, these are all the solutions to the given equations.
[tex]\[ 2^m \times \left(\frac{1}{8}\right)^n = 128 \][/tex]
[tex]\[ 4m \div 2 - 4m = \frac{1}{16} \][/tex]
We'll approach this step by step.
### Step 1: Simplify the Second Equation
Starting with the second equation:
[tex]\[ 4m \div 2 - 4m = \frac{1}{16} \][/tex]
Dividing \( 4m \) by 2 simplifies to \( 2m \):
[tex]\[ 2m - 4m = \frac{1}{16} \][/tex]
Combine like terms:
[tex]\[ -2m = \frac{1}{16} \][/tex]
Solving for \( m \):
[tex]\[ m = -\frac{1}{32} \][/tex]
### Step 2: Substitute \( m \) into the First Equation
Now, we substitute \( m = -\frac{1}{32} \) into the first equation:
[tex]\[ 2^m \times \left(\frac{1}{8}\right)^n = 128 \][/tex]
First, express \( \frac{1}{8} \) as a power of 2:
[tex]\[ \frac{1}{8} = 2^{-3} \][/tex]
The first equation now becomes:
[tex]\[ 2^m \times (2^{-3})^n = 128 \][/tex]
Simplify the exponent on the left side:
[tex]\[ 2^m \times 2^{-3n} = 128 \][/tex]
Combine the exponents:
[tex]\[ 2^{m-3n} = 128 \][/tex]
Now, express 128 as a power of 2:
[tex]\[ 128 = 2^7 \][/tex]
So the equation simplifies to:
[tex]\[ 2^{m - 3n} = 2^7 \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ m - 3n = 7 \][/tex]
### Step 3: Solve for \( n \) using \( m = -\frac{1}{32} \)
Substitute \( m = -\frac{1}{32} \) into the exponent equation:
[tex]\[ -\frac{1}{32} - 3n = 7 \][/tex]
Add \(\frac{1}{32}\) to both sides:
[tex]\[ -3n = 7 + \frac{1}{32} \][/tex]
To add the fractions, convert 7 to a fraction with the same denominator:
[tex]\[ 7 = \frac{224}{32} \][/tex]
So:
[tex]\[ -3n = \frac{224}{32} + \frac{1}{32} \][/tex]
[tex]\[ -3n = \frac{225}{32} \][/tex]
Divide both sides by -3:
[tex]\[ n = -\frac{225}{32 \times 3} \][/tex]
[tex]\[ n = -\frac{225}{96} \][/tex]
Simplify \(-\frac{225}{96}\):
[tex]\[ n = -\frac{225}{96} = -\frac{75}{32} \][/tex]
### Step 4: Box the Solutions
We have found that:
[tex]\[ m = -\frac{1}{32} \][/tex]
[tex]\[ n = -\frac{75}{32} \][/tex]
So, the solutions are:
[tex]\[ m = -0.03125 \][/tex]
[tex]\[ n = -2.34375 \][/tex]
Comparing this with the given results, we have the following possible solutions:
1. \( m = -0.03125 \), \( n = -2.34375 \)
2. \( m = -0.03125 \), \( n = -2.34375 - 3.0215734278848i \)
3. \( m = -0.03125 \), \( n = -2.34375 + 3.0215734278848i \)
Thus, these are all the solutions to the given equations.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.